Immune-unreactive urinary albumin as a predictor of cardiovascular events: the Hortega Study. Issue 4 (16th May 2018) - Martínez, Fernando; Pichler, Gernot; Ruiz, Adrian; Martín-Escudero, Juan C; Chaves, Felipe J; Gonzalez-Albert, Veronica; Tellez-Plaza, Maria; Heerspink, Hiddo J L; Zeeuw, Dick D E; Redon, Josep
Abstract: Background: We aimed to determine if immune-unreactive albumin excretion (IURAE) is associated with cardiovascular (CV) events in a representative sample of a general population from Spain. Methods: We included 1297 subjects (mean age ± standard error 48.0 ± 0.2 years, 48% females), who participated in the Hortega Follow-Up Study. The primary endpoint was incidence of fatal and non-fatal CV events. Urinary albumin excretion (UAE) was measured in spot voided urine, frozen at –80°C, by immunonephelometry [immune-reactive albumin excretion (IRAE)] and by high-performance liquid chromatography (HPLC) [total albumin excretion (AE)]. IURAE was calculated as the difference between HPLC measurements and IRAE. We estimated fully adjusted hazard ratios (HRs) of CV incidence by Cox regression for IRAE, IURAE and total AE. Results: After an average at-risk follow-up of 13 years, we observed 172 CV events. urinary albumin to creatinine ratio (UACR) of ≥30 mg/g assessed by IRAE, IURAE or total AE concentrations was observed in 74, 273 and 417 participants, respectively. Among discordant pairs, there were 49 events in those classified as micro- and macroalbuminuric by IURAE, but normoalbuminuric by IRAE. Only the IRAE was a significant independent factor for the incidence of CV events [HR (95% confidence interval) 1.15 (1.04–1.27)]. The association of UAE with CV events was mainly driven by heart failure (HF) [HR 1.33 (1.15–1.55) for IRAE; HR 1.38 (1.06–1.79) for IURAE; HR 1.62 (1.22–2.13) for total AE]. Those subjects who were micro- and macroalbuminuric by both IRAE and IURAE had a significant increase in risk for any CV event, and especially for HF. Conclusions: IRAE, IURAE and AE were associated with an increased risk for CV events, but IRAE offered better prognostic assessment.